2011
DOI: 10.1007/s00347-011-2411-0
|View full text |Cite
|
Sign up to set email alerts
|

Einfluss verschiedener multifokaler Intraokularlinsenkonzepte auf den Streulichtparameter

Abstract: Stray light and subjective photopic phenomena do not show any basic correlation. Measurements in patients with refractive MIOLs showed less stray light than near segment or diffractive MIOLs. However, refractive MIOLs induced more halos compared to the other groups analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
3
6
0
5
Order By: Relevance
“…2 . Indeed, almost all eyes (30 eyes, 96.8%) had a postoperative spherical equivalent within ±1.00 D. Similar visual and refractive results were obtained by Bautista et al [11] using the same modality of diffractive IOL and by other authors [2, 3, 4] using other types of diffractive multifocal IOLs. Specifically, Bautista et al [11] found in a sample of 70 eyes of 70 patients a mean far LogMAR UCVA of 0.194 ± 0.054, 0.119 ± 0.026, and 0.076 ± 0.014 at 15, 30, and 60 days after surgery, respectively.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…2 . Indeed, almost all eyes (30 eyes, 96.8%) had a postoperative spherical equivalent within ±1.00 D. Similar visual and refractive results were obtained by Bautista et al [11] using the same modality of diffractive IOL and by other authors [2, 3, 4] using other types of diffractive multifocal IOLs. Specifically, Bautista et al [11] found in a sample of 70 eyes of 70 patients a mean far LogMAR UCVA of 0.194 ± 0.054, 0.119 ± 0.026, and 0.076 ± 0.014 at 15, 30, and 60 days after surgery, respectively.…”
Section: Resultssupporting
confidence: 83%
“…The latest models of these types of IOLs have been shown to provide good distance and near functional vision without the patient having to wear corrective lenses [2, 3]. However, some optical side effects have been reported with some models of multifocal IOLs such as decreased contrast sensitivity, glare disability or halos [4, 5]. …”
Section: Multifocal Diffractive Technologymentioning
confidence: 99%
“…La reproductibilité de cette plateforme a également été prouvée dans la littérature par Guber et al [10] et Cervino et al [23]. Elle permet l'analyse de la diffusion antérograde de la lumière et a essentiellement été utilisée pour l'étude de la qualité de vision après chirurgie réfractive (après Epilasik et Lasik par Li et al [24], pour mesurer l'effet d'implants de chambre postérieure par Ehmer et al [25] et Xing et al [26], l'étude de glistennings sur les implants de chambre postérieure par Colin et al [27]. .…”
Section: Discussionunclassified
“…de Vries et al found a small but significant lower straylight in monofocal lenses, and concluded this was caused by the diffractive pattern of the multifocal IOL [19]. Ehmer et al found that refractive multifocal IOLs have less straylight, but more halos and subjective complaints than diffractive or segment addition IOLs; however, each study group consisted of only 10 eyes [7]. Glistenings as a source of increased straylight in the hydrophobic (control) group versus the hydrophilic (study) group is probably not the cause for the difference in straylight.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, with these lenses visual side-effects are reported between 10–18 %, which is not dissimilar to apodized diffractive IOLs [46]. In any type of multifocal IOL in which the image is split into two images that are seen simultaneously, one image will be clear, while the other is hardly perceived or blurred, which in diffractive lenses is usually called the blur circle [3], and is also found in parallel complaints with radially asymmetric lenses [7, 8]. These asymmetric lenses have also been known to cause visual side-effects, which are treated by changing the direction of implantation; with the sectorial addition upward, or by inserting a capsular tension ring to reduce tilt and decentration [9].…”
Section: Introductionmentioning
confidence: 99%